2022
DOI: 10.1155/2022/1349994
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Management, and Outcomes of Community-Acquired Pneumonia Due to Human Rhinovirus—A Retrospective Study

Abstract: Introduction. Human rhinovirus (HRV) can lead to a variety of respiratory illnesses; it is also an uncommon cause of community-acquired pneumonia (CAP). We described the characteristics and outcomes of patients hospitalized for CAP due to HRV. Methods. We retrospectively studied consecutive adult patients admitted to King Abdulaziz Medical City-Riyadh with CAP due to HRV between 2016 and 2019. The diagnosis was made by respiratory multiplex PCR within 48 hours of hospitalization. We compared patients requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The persistence of rhinovirus, however, is a source of concern regardless of its cause. Indeed, this virus is now viewed as a truly pathogenic microorganism 32 34 , and its economic and social impact has been shown to be as significant as that of influenza 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of rhinovirus, however, is a source of concern regardless of its cause. Indeed, this virus is now viewed as a truly pathogenic microorganism 32 34 , and its economic and social impact has been shown to be as significant as that of influenza 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Hospital acquired pneumonia (HAP) which is defined as that acquired after a minimum of 48 hours stay in the hospital, Community acquired pneumonia refers to that contracted outside the hospital setting or before 48 hours of stay in the hospital [3]. It is a leading cause of sepsis [4], accounting for an ample portion of the global infectious diseases burden, mortality and morbidity; especially in resources challenged countries [5]. The World Health Organization (WHO) estimates the annual global mortality arising from Community acquired pneumonia at between three and four million [6].…”
Section: Introductionmentioning
confidence: 99%
“…Data on pneumonia caused by viruses other than Middle East respiratory syndrome coronavirus and severe acute respiratory syndrome coronavirus 2 in Middle Eastern populations are scarce [23,24]. A study on patients with viral pneumonia in a tertiary-care hospital in Riyadh found that the most commonly identified virus was influenza A (non-H1N1)/influenza B (216 patients), followed by H1N1 influenza (150 patients), and Middle East respiratory syndrome coronavirus (82 patients) [23].…”
Section: Introductionmentioning
confidence: 99%